Medical expertise as a critical influencing factor on the length of stay in the ED: A retrospective cohort study. Issue 19 (14th May 2021) - Trotzky, Daniel; Tsur, Avishai M.; Fordham, Daniel E.; Halpern, Pinchas; Ironi, Avinoah; Ziv-Baran, Tomer; Cohen, Aya; Rozental, Lior; Or, Jacob
Abstract : Abstract: Overcrowding in the emergency departments (ED) is a significant issue associated with increased morbidity and mortality rates as well as decreased patient satisfaction. Length of stay (LOS) is both a cause and a result of overcrowding. In Israel, as there are few emergency medicine (EM) physicians, the ED team is supplemented with doctors from specialties including internal medicine, general surgery, orthopedics etc. Here we compare ED length of stay (ED-LOS), treatment time and decision time between EM physicians, internists and general surgeons. A retrospective cohort study was conducted examining the Emergency Department length of stay (ED-LOS) for all adult patients attending Sheba Medical Center ED, Israel, between January 1st, and December 31st, 2014. Using electronic medical records, data was gathered on patient age, sex, primary ED physician, diagnosis, eventual disposition, treatment time and disposition decision time. The primary outcome variable was ED-LOS relative to case physician specialty and level (ED, internal medicine or surgery; specialist or resident). Secondary analysis was conducted on time to treatment/ decision as well as ED-LOS relative to patient classification variables (internal medicine vs surgical diagnosis). Specialists were compared to specialists and residents to residents for all outcomes. Residents and specialists in either EM, internal medicine or general surgery attended 57, 486 (51.50%) of 111, 630 visits to Sheba Hospital's general ED. Mean ED-LOS was 4.12 ± 3.18 hours. Mean treatment time and decision time were 1.79 ± 1.82 hours, 2.84 ± 2.17 hours respectively. Amongst specialists, ED-LOS was shorter for EM physicians than for internal medicine physicians (mean difference 0.28 hours, 95% CI 0.14–0.43) and general surgeons (mean difference 0.63 hours, 95% CI 0.43–0.83). There was no statistical significance between residents when comparing outcomes. Increasing the number of EM specialists in the ED may support efforts to decrease ED-LOS, overcrowding and medical errors whilst increasing patient satisfaction and outcomes.